Effect of Biomass Composition and Co-pyrolysis Retention Time on Reduction of Non-neutral CO2 Emission from Combustion of Hybrid Coal in Power Plant. (June 2019) - Handoko, S; Wulandari, W; Rizkiana, J; Ridha, M A; Prasetyo, H A; Sasongko, D
Abstract: Indonesia's lignite coal and sawdust production are 131, 05 and 11, 82 million tonnes, respectively, which are potential to become raw material of hybrid coal through co-pyrolysis. Hybrid coal utilization will reduce non-neutral CO2 emission, a part of CO2 emission released from combustion of biomass. The aim of this study is to determine the effects on biomass composition and co-pyrolysis retention time on reduction of non-neutral CO2 emission from combustion of hybrid coal in power plant. Co-pyrolysis was conducted in a vertical tubular furnace under an inert condition in atmospheric pressure and temperature 300° C. Biomass composition and co-pyrolysis retention time was varied from 20 to 40 %-mass and from 30 to 90 minutes, respectively. Hybrid coal was characterized with proximate, ultimate and calorific value analysis. The result of analysis was used as an input on simulation to determine reduction of non-neutral CO2 emission on hybrid coal combustion in power plant. An increase in co-pyrolysis retention time (CRT) from 30 to 90 minutes increases the CO2 emission from 13.25 to 13.30 %-vol. While increase in biomass composition from 20 to 40 %-mass reduce CO2 emission from 13.18 to 12.81 %-vol. Non-neutral CO2 emission reduction rises from 24.22 to 26.86 % along with the increased of biomass composition from 20 to 40 %-mass. Average of non-neutral CO2 emission reduction is about 26.30 % in all variation. CO2 emission of hybrid coal as fuel for power plant increased along with the increased of co-pyrolysis retention time (CRT), which was about 780-830 kg CO2 /MWh. The highest CO2 emission was achieved from co-pyrolysis product hybrid coal utilization with 30 %-mass of biomass composition.